Peer review of a cancer weight of evidence assessment based on updated toxicokinetics, genotoxicity, and carcinogenicity data for 1, 3-dichloropropene using a blinded, virtual panel of experts. (25th November 2020) - Hays, Sean M.; Nelson, Dawn M.; Kirman, Christopher R.
Abstract: A cancer weight of evidence (WOE) analysis based on updated toxicokinetics, genotoxicity, and carcinogenicity data for 1, 3-dichloropropene was peer reviewed by a panel of experts. Historically, 1, 3-dichloropropene has been classified in the U.S. as "likely to be carcinogenic to humans" via oral and inhalation exposure routes based upon the results of rodent cancer bioassays conducted in the 1980s. Contemporary studies led the authors of the WOE analysis to conclude that the currently manufactured form of 1, 3-dichloropropene is not mutagenic and not carcinogenic below certain doses, pointing to a threshold-based approach for cancer risk assessment. SciPinion conducted a peer review of the WOE analysis using methods for assembling and managing blinded expert panels that maximize expertise while minimizing potential selection/participation bias. The process was implemented through a web-based application that poses a series of questions soliciting the experts' scientific opinions and observations about specific topics. The goal of the peer review was to have experts provide conclusions about the WOE for carcinogenicity classification of 1, 3-dichloropropene, identify potential data gaps, and evaluate the validity of a threshold-based risk assessment for 1, 3-dichloropropene. Based on a robust peer review of the current scientific information, a cancer WOE classification of "not likely to be carcinogenic to humans" is best supported for 1, 3-dichloropropene. This conclusion is reached with a high degree of consensus (consensus score = 0.92) across expert panel members.